Selection of reference genes for quantitative real-time PCR expression studies of microdissected reproductive tissues in apomictic and sexual Boechera - Amiteye Samuel; Mau Martin; Sharbel Timothy F; Pellino Marco; Corral José (BMC Research Notes, 2011)
Abstract Background Apomixis, a natural form of asexual seed production in plants, is considered to have great biotechnological potential for agriculture. It has been hypothesised that de-regulation of the sexual developmental pathway could trigger apomictic reproduction. The genus Boechera represents an interesting model system for understanding apomixis, having both sexual and apomictic genotypes at the diploid level. Quantitative qRT-PCR is the most extensively used method for validating genome-wide gene expression analyses, but in order to obtain reliable results, suitable reference genes are necessary. In this work we have evaluated six potential reference genes isolated from a 454 (FLX) derived cDNA library of Boechera. RNA from live microdissected ovules and anthers at different developmental stages, as well as vegetative tissues of apomictic and sexual Boechera, were used to validate the candidates. Results Based on homologies with Arabidopsis, six genes were selected from a 454 cDNA library of Boechera: RPS18 (Ribosomal sub protein 18), Efalpha1 (Elongation factor 1 alpha), ACT 2 (Actin2), UBQ (polyubiquitin), PEX4 (Peroxisomal ubiquitin conjugating enzyme) and At1g09770.1 (Arabidopsis thaliana cell division cycle 5). Total RNA was extracted from 17 different tissues, qRT-PCRs were performed, and raw Ct values were analyzed for primer efficiencies and gene ratios. The geNorm and normFinder applications were used for selecting the most stable genes among all tissues and specific tissue groups (ovule, anthers and vegetative tissues) in both apomictic and sexual plants separately. Our results show that BoechRPS18, BoechEfα1, BoechACT2 and BoechUBQ were the most stable genes. Based on geNorm, the combinations of BoechRPS18 and BoechEfα1 or BoechUBQ and BoechEfα1 were the most stable in the apomictic plant, while BoechRPS18 and BoechACT2 or BoechUBQ and BoechACT2 performed best in the sexual plant. When subgroups of tissue samples were analyzed, different optimal combinations were identified in sexual ovules (BoechUBQ and BoechEfα1), in anthers from both reproductive systems (BoechACT2 and BoechEfα1), in apomictic vegetative tissues (BoechEfα1 and BoechACT2) and sexual vegetative tissues (BoechRPS18 and BoechEfα1). NormFinder ranked BoechACT2 as the most stable in the apomictic plant, while BoechRPS18 was the best in the sexual plant. The subgroups analysis identified the best gene for both apomictic and sexual ovules (BoechRPS18), for anthers from both reproductive system (BoechEfα1) and for apomictic and vegetative tissues (BoechACT2 and BoechRPS18 respectively) Conclusions From a total of six tested genes, BoechRPS18, BoechEfα1, BoechACT2 and BoechUBQ showed the best stability values. We furthermore provide detailed information for the accurate normalization of specific tissue gene expression analyses of apomictic and sexual Boechera.